3-D physical model in strong ground motion numerical simulation： A case study of Kunming basin - 张冬丽 徐锡伟 赵伯明 陈桂华 解廷伟 (Acta seismologica sinica, 2007)
Seismic hazard assessment based on urban active faults can provide scientific bases for city planning and project construction, while numerical simulation of strong ground motion is an important method for seismic hazard prediction and assessment. A 3-D physical model in conformity with real strata configuration of （mainly） the Quaternary is a prerequisite to ensure the reliability of the simulation results. In this paper, we give a detailed account of the technical scheme and process for creating a 3-D physical model in Kunming basin. The data used are synthe- sized from seismogeological data, borehole data, topographic data, digital elevation mode （DEM） data, seismic exploration results and wave velocity measurements. Strafigraphic division is based mainly on shear wave velocity, with strata sequence taken into consideration. The model construction is finally accomplished with ArcGIS and many relevant programming techniques via layer-by-layer stacking （in depth direction） of the adjacent medium interfaces （meshes）. Meanwhile, a database of 3-D physical models is set up, which provides model data and parameters for strong ground motion simulation. Some processing methods and significant issues are also addressed in the paper in accordance with different types of exploration and experimental data.